DEVELOPING THE ASSESSMENT INSTRUMENT OF SPEAKING - Ahmad Ghufran Ferdiant (IAIN MADURA, 2016)
Speaking means to express ideas orally. By expressing what is in mind, a speaker can make others understand things inside his/her mind. In order to make the others capture and understand what he/she expresses orally, a student should needs to pay attention on the signs that should be fulfilled. How to develop the assessment instrument of the students’ speaking ability? Therefore the writer used qualitative research design to describe the way to develop the assessment instrument of the students’ ability. The result showed that Developing speaking test is not as easy as other tests because a test developer has to prepare the mechanism or direction and instruction well in order to keep the test valid in which the test developer used content validity to prove that the test was valid. In keeping the reliability the test developer used inter- rater and Pearson Product Moment formula. In fact, content validity, inter-rater and Pearson Product moment formula are proper to assess speaking test. This study will be useful for the English teachers in increasing the ability of the students in speaking by assessing the students’ capability in good ways.